ChemInform Abstract: Hydrogenation of (N, N‐Disubstituted Aminomethyl)nitrobenzenes to (N, N‐Disubstituted Aminomethyl)anilines Catalyzed by Palladium—Nickel Bimetallic Nanoparticles. Issue 40 (October 2015) - Bao, Hailin; Wang, Dingsheng; Wang, Xinyan; Cheng, Chuanjie; Li, Yadong; Hu, Yuefei
Abstract A stable nanosized Pd‐Ni bimetallic catalyst is prepared by heating Raney‐Ni and Na2PdCl4 in water.